Alcohol reduces the activity of somatostatin interneurons in the mouse prefrontal cortex: A neural basis for its disinhibitory effect?. (1st May 2021) - Li, Miao; Cabrera-Garcia, David; Salling, Michael C.; Au, Edmund; Yang, Guang; Harrison, Neil L.
Abstract: The prefrontal cortex (PFC) is involved in executive ("top-down") control of behavior and its function is especially susceptible to the effects of alcohol, leading to behavioral disinhibition that is associated with alterations in decision making, response inhibition, social anxiety and working memory. The circuitry of the PFC involves a complex interplay between pyramidal neurons (PNs) and several subclasses of inhibitory interneurons (INs), including somatostatin (SST)-expressing INs. Using in vivo calcium imaging, we showed that alcohol dose-dependently altered network activity in layers 2/3 of the prelimbic subregion of the mouse PFC. Low doses of alcohol (1 g/kg, intraperitoneal, i.p.) caused moderate activation of SST INs and weak inhibition of PNs. At moderate to high doses, alcohol (2–3 g/kg) strongly inhibited the activity of SST INs in vivo, and this effect may result in disinhibition, as the activity of a subpopulation of PNs was simultaneously enhanced. In contrast, recordings in brain slices using ex vivo electrophysiology revealed no direct effect of alcohol on the excitability of either SST INs or PNs over a range of concentrations (20 and 50 mM) consistent with the blood alcohol levels reached in the in vivo experiments. This dose-dependent effect of alcohol on SST INs in vivo may reveal a neural basis for the disinhibitory effect of alcohol in the PFC mediated by other neurons within or external to the PFC circuitry. Highlights: In vivo calcium imaging enables study of alcohol in the prefrontal cortex (PFC). High dose alcohol increases the activity of pyramidal neurons (PNs). High dose alcohol decreases the activity of somatostatin (SST) interneurons (INs). Excitability of SST INs and PNs is unaltered by acute alcohol ex vivo. SST INs may mediate a disinhibitory effect of acute alcohol in the PFC.